Evaluation of different soy protein concentrate sources on growth performance of weanling pigs - N A Lenehan; M R Barker; N Z Frantz; C N Groesbeck; T Iwasawa; T P Keegan; K R Lawrence; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2003)
Three experiments were conducted using 486 weanling pigs (216 in Experiment 1; 210 in Experiment 2; 60 in Experiment 3) to determine the effects of different soy protein concentrate (SPC) sources on growth performance. Soy protein concentrate source 1 is dried with a torus disk following the concentration of soy proteins. This drying procedure will generate some degree of heat and possibly mechanical forces somewhat similar to extrusion processing (Soycomil PÂ®, ADM). Soy protein concentrate source 2 is dried by a different process, and then it is moist extruded (Profine E, Central Soya). Therefore, the objective of our study was to determine the relative feeding value of the different SPC sources compared with a complex diet containing milk and other specialty proteins (no soy protein), or a diet containing 40% soybean meal. In Experiment 1, each SPC source (28.6%) replaced all the soybean meal (SBM) in the control diet on a lysine basis. Pigs fed the diet containing 40% SBM had similar performance to pigs fed the milk-protein based diet from d 0 to 14. Pigs fed either SPC source had lower ADG and ADFI compared to pigs fed either the diet containing 40% SBM or the milkprotein based diet. Pigs fed the diet containing 40% SBM and SPC from source 2 had better F/G than pigs fed the milk-protein based diet or SPC from source 1. In Experiment 2, either all or half of the soybean meal was replaced by the 28.6 or 14.3% SPC from source 1 and 2. From d 0 to 14 and d 0 to 28, an SPC source by level interaction was observed for ADG (P<0.01) and ADFI (P<0.07). Replacing soybean meal with SPC from source 1 did not influence pig performance. However, replacing soybean meal with SPC from source 2 resulted in a quadratic (P<0.05) improvement in ADG with performance being improved for the diet containing 14.3% SPC, but no benefit to replacing all the soybean meal with SPC. Replacing soybean meal with SPC from either source influenced feed efficiency in a quadratic (P<0.01) manner with feed efficiency being optimal for pigs consuming the diet with half the soybean meal replaced by SPC. Because replacing all of the soybean meal with SPC reduced ADFI in Experiments 1 and 2, we hypothesized that pigs may not prefer the taste of a diet with a high inclusion rate of SPC (28.6%). To test this theory, a 7-day preference test was conducted to determine feed intake of weanling pigs provided the option of consuming diets containing either 40% soybean meal or 28.6% SPC (from source 2). Average daily feed intake was 0.41 and 0.01 lb for the 40% soybean meal and 28.6% soy protein concentrate diets, respectively (P<0.0001). The poor intake of the SPC diet may indicate a palatability problem when high levels of SPC are included in the diet. Our results suggest replacing a portion of the soybean meal in the diet with SPC from source 2 improves ADG and feed efficiency; however, high levels (28.6%) of SPC should not be included in the diet.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Swine; Pigs; Soy protein; Lysine